Exploring the use of workshops to encourage educators to use online learning platforms. - Shotter, Melanie (The IIE, 2017)
This study investigates, through a quantitative research design, the effect of an intervention workshop applied to tertiary educators who appeared to underutilize an advantageous online educational learning platform. In order to bring about this investigation, an anonymous cross-sectional survey was administrated to 15 educators to determine the amount of usage, underutilization and possible causes for such. Through a confidence level of 95%, with a Margin of Error of plus/minus 5%, results from this data received showed that an intervention workshop can be implemented to arouse an encouraged use of the online learning platform (Smith, 2013). These results are reflected through statistical representation of graphs, charts and diagrams in this research article.
Keywords: Lecturer development; Educational learning platform; Educational technology; Teaching and learning